Hurricane Shutter-Related Injuries Treated in Emergency Departments. (11th June 2021) - Forrester, Mathias B.
ABSTRACT: Objectives: Injuries may occur when putting up and taking down hurricane (storm) shutters. This study described hurricane shutter-related injuries managed at emergency departments (EDs). Methods: Hurricane shutter-related injuries were identified through the National Electronic Injury Surveillance System (NEISS), a database of consumer product-related injuries collected from the EDs of approximately 100 United States hospitals. Results: There were 329 hurricane shutter-related injuries during 2001-2017. Thirty-six injuries were reported during October 2005 (Hurricane Wilma), 30 during August 2008 (Tropical Storm Fay), and 103 during September 2017 (Hurricane Irma). Patients were 20 years or older in 90.6% of the cases; 76.3% of the patients were male. The most frequently reported injuries were laceration (48.9%), sprain or strain (15.2%), and fracture (9.4%). Lower extremities (34.0%) were the most commonly affected body part followed by upper extremities (29.5%) and head or neck (17.0%). The patient was treated or examined at the ED and released in 86.6% of the cases. Conclusions: Over half of the hurricane shutter-related injuries appeared to occur in association with hurricanes and tropical storms. The most frequently reported injuries were laceration followed by sprain or strain and fracture. The majority of patients were treated or examined at the ED and released.